Compliance to handwashing during the early phase of COVID-19 epidemic in Uganda: A nationwide cross-sectional survey - Richard Migisha; Bob Omoda Amodan; Lilian Bulage; Elizabeth Katana; Joseph Nelson Siewe Fodjo; Robert Colebunders; Alex Riolexus Ario; Rhoda Kitti Wanyenze (Journal of Interventional Epidemiology and Public Health)
Introduction: Handwashing is a low-cost, high-impact strategy for limiting the transmission of COVID-19. We assessed the level of compliance to handwashing and associated factors, among Ugandan residents, in the first two months of the outbreak in Uganda, to inform prevention measures.